STRATEGI PEMASARAN PRODUK PABRIK MINI CHOKATO (STUDI KASUS DI KELURAHAN KAPALO KOTO KECAMATAN PAYAKUMBUH SELATAN ) - Tarumun, Suardi; ', Yohannes F.S; ', Cepriadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The growth of cocoa in Indonesia has significant impact to entrepreneurs who process cocoa beans into refined products. The Company can not avoid the problems such as the changing business environment whether comes out from internal or external environment of the company. To minimize the problem, the manager should be able to develop appropriate marketing strategies. The goal is that the business carried on to survive and thrive. The purpose of this study was to identify the internal and external factors faced by Factory Mini Chokato and determine marketing strategies and also the priority of marketing strategy of refined products of Factory Mini Chokato. This study using the methods of descriptive qualitative to analyze the first goal and quantitative to analze the second goal. Data were collected from people who is considered as an expert in this study.The results of this study showed that the internal factors of the company that has impact in winning its product from the competition in the market is the quality of the cocoa product itself, the brand name, the strategic location for production, the ability to maintain relationship with stakeholders and a variety of products such as product packaging, promotional activities, product pricing, distribution channels and production capacity. The external factors include opportunities (availability of raw materials, technology development, local government support, healthy lifestyle community and industry competition level) and threats (decline in purchasing power, rising prices of basic necessities, rising energy costs and the existence of substitution products). The priority of marketing strategy of Factory Mini Chokato products is the process of production using the latest technology in order to increase production capacity and market demand and this is met with a priority value (0.286) using the expert choice in 2000 . Keywords : cocoa products, internal and external factors, SWOT, marketing strategy